Seamsar: Seamless And Secure Handover Model For Mobile IPTV Using MIPV6 - Cornelis, Armanda Caesario (2011)
Multimedia becomes one of the most wanted content in the modern Internet world. Since the Mobile Internet Protocol version 6 (MIPv6) was proposed until today many researchers have been trying to develop methods and protocols, in order to improve the performance of mobile multimedia services. Handover is a transition process when a Mobile Node (MN) moves from home network towards foreign network. This transition causes a latency that affected the data delivery. In mobile multimedia service, extensive latency in data delivery may introduce inconveniences on the user’s side.